2012
DOI: 10.1021/jp300055c
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Fluorescence and Phosphorescence Study of the Interaction of Brompheniramine with Human Serum Albumin

Abstract: Binding of the antihistamine drug brompheniramine (BPA) to human serum albumin (HSA) is studied by measuring quenching of the fluorescence and room temperature phosphorescence (RTP) of tryptophan. The modified Stern-Volmer equation was used to derive association constants and accessible fractions from the steady-state fluorescence data. Decay associated spectra (DAS) revealed three tryptophan fluorescence lifetimes, indicating the presence of three HSA conformations. BPA causes mainly static quenching of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Various fluorescence techniques have been used in the past to investigate the interactions between different drugs and proteins, with special attention to HSA. In addition to steady-state fluorescence quenching, [16][17][18][19][20][21][22][23][24] time-resolved measurements [25][26][27] allow the characterisation of the involved dynamic processes. In particular, femtosecond emission [28][29][30][31][32] constitutes a powerful tool for determining the very fast photo-initiated processes.…”
Section: Introductionmentioning
confidence: 99%
“…Various fluorescence techniques have been used in the past to investigate the interactions between different drugs and proteins, with special attention to HSA. In addition to steady-state fluorescence quenching, [16][17][18][19][20][21][22][23][24] time-resolved measurements [25][26][27] allow the characterisation of the involved dynamic processes. In particular, femtosecond emission [28][29][30][31][32] constitutes a powerful tool for determining the very fast photo-initiated processes.…”
Section: Introductionmentioning
confidence: 99%
“…indicated that the D increases with the pH value of aqueous phase. The possible reason is that the amount of molecular BPA increases with the rising of pH and molecular BPA preferentially distributes in organic phase. Simultaneously, α gradually increases with the pH value of aqueous phase when the pH value is lower than 7.50, and then slightly reduces when the pH was over 7.50.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is not possible to conclude whether BPA (in its protonated and neutral form) enters preferably in site I or site II. To answer this question, we investigated the complexation in a separate study of the BPA–HSA system by W214 phosphorescence: a strong quenching by BPA is observed which can be explained assuming a close proximity between BPA and W214 …”
Section: Resultsmentioning
confidence: 99%